Free surface electrospun fibers: The combined effect of processing parameters. Issue 1 (28th March 2013) - Han, Wanli; Nurwaha, Deogratias; Li, Chulin; Wang, Xinhou
<x xml:space="preserve">Abstract</x> In this study, a free surface electrospinning experimental setup was developed based on rotating spiral copper wire electrode and used as the spinneret. The scheme was investigated by varying processing parameters including polymer solution concentration, distance between the electrode and the collector, applied voltage between the electrode, and the collector and wire electrode diameter. An average of fiber diameter ranged between 202 and 543 nm and a relative standard deviation ranged between 11.0 and 26.9% were obtained. The combined effects of processing parameters on the resulting fiber morphology were investigated. The analysis shows that in a multiple variable process like electrospinning, the interaction between the different processing parameters played an important role, rather than one parameter separately in obtaining desired nanofibers. Knowing the relative combined effects of processing parameters on fiber morphology should be useful for process control and prediction of electrospun fiber quality as it has been demonstrated in this study. POLYM. ENG. SCI., 54:189–197, 2014. © 2013 Society of Plastics Engineers